Perilaku Maladministrasi Birokrasi Dalam Pelayanan Publik di Kota Pekanbaru, Provinsi Riau: Faktor Penyebab dan Solusinya - Rodi Wahyudi; Jalaluddin Abdul Malek; Azmi Aziz (Centre for Public Policy and Management Studies, 2015)
Changes in the system of government and bureaucratic reforms have not been able to prevent maladministration in the bureaucratic behavior in Indonesia. The question is whether this type of behavior exists in public service in the city of Pekanbaru. The purpose of this study is to investigate the causes of such behavior in government institutions that provides document services directly to the public and whether it has a back up solution to prevent bureaucratic maladministration behavior. Questionnaires were distributed to 250 employees of Population and Civil Registration, Office of Integrated Services and Investment, Immigration Office Class I, Office SAMSAT and sub-district office employees in the city of Pekanbaru. Quantitative analysis of this study reinforced the result of a depth interview conducted with 5 key informants, a supporting method employed in this research. The research revealed that bureaucratic maladministration behavior is caused by heredity bureaucratic culture where the institutions eventually discharge employees who have low labor productivity and shift the mind set of employees in order to improve the quality of service.